2012
DOI: 10.1021/ie201397a
|View full text |Cite
|
Sign up to set email alerts
|

Simplified Methodology for the Design and Optimization of Thermally Coupled Reactive Distillation Systems

Abstract: New intensified schemes have been recently proposed as an attempt to reduce energy requirements and equipment costs in reaction−separation processes. A design methodology for thermally coupled reactive distillation systems is proposed in this work. To design the columns, a method based on the Fenske−Underwood−Gilliland (FUG) equations is proposed and tested. The FUG equations, the mass and energy balances, and the phase equilibrium equations are used to formulate the model of the intensified systems. Such a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The number of theoretical stages, the minimum reflux ratio, and the feed stage estimated position were determined, by preliminary simulations, using the Shortcut column method from the PRO/II 33 simulation software. In this method, the calculation of the preliminary parameters are performed thus: the minimum number of stages by Fenske method, the minimum reflux ratio by Underwood method, the number of theoretical stages by Gilliland correlation, and the estimation of the feed stage by Kirkbride equation 44,45 . The Shortcut column method is a useful tool for preliminary design when it is properly applied.…”
Section: Methodsmentioning
confidence: 99%
“…The number of theoretical stages, the minimum reflux ratio, and the feed stage estimated position were determined, by preliminary simulations, using the Shortcut column method from the PRO/II 33 simulation software. In this method, the calculation of the preliminary parameters are performed thus: the minimum number of stages by Fenske method, the minimum reflux ratio by Underwood method, the number of theoretical stages by Gilliland correlation, and the estimation of the feed stage by Kirkbride equation 44,45 . The Shortcut column method is a useful tool for preliminary design when it is properly applied.…”
Section: Methodsmentioning
confidence: 99%
“…The DWCs for ternary separations have been widely studied, and many applications demonstrated that energy consumption can be reduced by 30–50 % compared to conventional columns . Remarkably, these DWC benefits are not limited to ternary separations alone, but they can be present also in azeotropic separations , , extractive distillation , , and reactive distillation , .…”
Section: Introductionmentioning
confidence: 99%
“…Control of an R-DWC is extraordinary more difficult than that of an RD column because of the inner complex structures of the R-DWC . The control of RD columns and DWCs has been studied by many researchers, but the control of R-DWCs has received less attention, and few studies of it have been reported. However, an R-DWC can be considered as the combination of an RD column and a DWC, so it might be useful to investigate the control of an RD column and a DWC in a study of the control of an R-DWC.…”
Section: Introductionmentioning
confidence: 99%